Shared Sporadic and Somatic Thyrotropin Receptor Mutations Display More Active In Vitro Activities than Familial Thyrotropin Receptor Mutations - GÖZÜ, HÜLYA (MARY ANN LIEBERT, INC, 2011)
Background: Germline thyrotropin receptor (TSHR) mutations are associated with sporadic congenital nonautoimmune hyperthyroidism and familial nonautoimmune hyperthyroidism. Somatic TSHR mutations are associated with toxic thyroid nodules (TTNs). The objective of the study was to define a relation of the clinical appearance and the in vitro activity (IVA) of the TSHR mutations described by several authors for these thyroid disorders. Methods: We analyzed the IVAs published as linear regression analysis (LRA) of the constitutive activity as a function of the TSHR expression and the basal cyclic adenosine monophosphate (cAMP) values to determine differences between exclusively somatic, exclusively familial, and shared sporadic and somatic TSHR-mutations. Further, we investigated correlations of the LRAs/basal cAMP values with clinical activity characteristics (CACs) of TTNs, such as largest diameter of the TTN and the age of the patient at thyroid surgery. Results: Shared sporadic and somatic mutations showed higher median LRA (14.5) and higher median basal cAMP values (fivefold) than exclusively familial mutations (6.1, p = 0.0002; 2.9-fold, p < 0.0001, respectively). Moreover, mutations shared between sporadic congenital nonautoimmune hyperthyroidism and toxic thyroid nodules (TTNs) showed higher median LRA/basal cAMP values (p < 0.0001) than exclusively somatic mutations in TTNs (5.1; 3.89-fold, respectively). Exclusively somatic mutations and exclusively familial mutations showed no significant difference in their median LRA values (p - 0.786) but a significant difference for basal cAMP values (p - 0.0006). The two examined CACs showed no correlation with the IVA characterized by LRA/basal cAMP values or with the presence or absence of a TSHR-mutation. Conclusions: This systematic analysis of published constitutively activating TSHR-mutations, their CACs, and their IVA provides evidence for higher IVA of shared sporadic and somatic TSHR mutations as compared with familial TSHR mutations. CACs of somatic TSHR mutations in TTNs did not have a clear association with the IVA as characterized by LRA or basal cAMP values.
Keywords: NON-AUTOIMMUNE HYPERTHYROIDISM; THYROID HYPERFUNCTIONING ADENOMAS; TERM-FOLLOW-UP; HEREDITARY NONAUTOIMMUNE HYPERTHYROIDISM; AUTOSOMAL-DOMINANT HYPERTHYROIDISM; ACTIVATING GERMLINE MUTATION; STIMULATING HORMONE-RECEPTOR; TOXIC MULTINODULAR GOITER; IODINE-DEFICIENT AREA; TSH RECEPTOR